Complications following Iliac Wing Fibrosarcoma - G. Stan; H. Orban; R. Deculescu (Case Reports in Orthopedics)
The aim of this case report is to underline surgical strategies for complications in a case of a young man with fibrosarcoma of the bone treated with pelvic resection followed by reconstruction with massive bone allograft. A type I pelvic resection was performed as a radical resection of tumor followed by a biological reconstruction of iliac wing using frozen allograft. The iliac allograft was fixed in place using 4 screws. The immediate postoperative period was complicated with local sepsis of reconstructed site treated with pediculate omentoplasty. After 1 year from surgery, the X-ray exam showed an integrated allograft. After 20 years from the first surgery, the patient presented with the left hip pain of 3-month duration with mechanical pattern. The X-ray and CT exam showed the left hip arthritis and no signs of recurrence. A total hip arthroplasty with dual mobility cup and uncemented stem was performed. Despite the immediate postoperative local infection, the allograft was left in place and integrated after all. Omentoplasty could be a very useful technique in eradicating local infection, due to the immunogenic properties of the omentum. The allograft is still strong enough to give support for a hip arthroplasty at 20 years after implantation.